The effects of doctors’ interpersonal communication on low-income inpatients’ satisfaction level - Effendi, Ridwan; Sukmayadi, Vidi; Pandjaitan, Irpanus Rachman (Penerbit Universiti Kebangsaan Malaysia, 2019)
Doctors' interpersonal communication skill is an integral part of health services and become one of the main indicators of patients’ satisfaction towards healthcare provider. This study aims at examining the influence of doctors' interpersonal communication on the satisfaction levels of class III (low income) inpatients at Hasan Sadikin Hospital, Bandung, Indonesia. The method applied in this study is quantitative method utilizing survey as study instrument and tool of analysis. There were 261 patients as the study population, and 72 randomly selected respondents were taken as the study sample. The authors used simple random sampling method in carrying out selection of patients in this study. The data were analyzed using the continuum line and multiple linear regression analysis, either simultaneously or partially. In the hypothesis test, F-test was conducted, and H1 was accepted. The results of the study indicated that there was an influence between the two variables. The respondents’ responses indicated that the doctors' interpersonal communication was in the category of a very high interpersonal skill. Moreover, the respondents also had a very high level of satisfaction with the health service. Thus, based on the findings, the doctors' interpersonal communication skills had a significant effect on low-income patients’ satisfaction levels simultaneously.